The cognitive effects of esketamine: what do we know so far? - M. Barbosa; R. Guedes (European Psychiatry, 2022)
Introduction Esketamine is an S-enantiomer of ketamine approved by the EMA for treatment-resistant depression (TRD). As an NMDA receptor antagonist, its administration results in increase of glutamate release and AMPA receptor activation, supporting both rapid-onset and long-term antidepressant effects. Short-term tolerability seems acceptable but major concerns remain regarding long-term safety, specifically regarding potential neurocognitive toxicity.